Import of small RNAs into Leishmania mitochondria in vitro. - Mahapatra, S (1994)
Using an in vitro ribonuclease protection assay, it was shown that synthetic antisense transcripts from the 5'-upstream region of the beta-tubulin gene are efficiently imported into isolated Leishmania mitochondria. Import occurred after a lag of about 30 min at 25 degrees C and was dependent on ATP. Preincubation experiments suggested that import consists of a slow interaction of mitochondria with RNA, followed by rapid ATP-dependent uptake. Import was saturable with antisense RNA at about 1 nM concentration, and sequence-specific, as shown by lack of import of other labelled transcripts. Deletion analysis demonstrated a correlation between efficiency of import and the number of oligopurine motifs on the antisense RNA. Several small ribosomal RNAs (srRNAs) and Leishmania tRNA competed with antisense RNA for import. Incubation of mitochondria with srRNAs and tRNA in the presence of radiolabelled UTP resulted in the ribonuclease-resistant labelling of these RNAs by the mitochondrial terminal uridylyl transferase. Extracts of isolated mitochondria contain a factor binding to antisense RNA, as shown by gel retardation assay. These observations indicate the presence of a receptor-mediated import pathway for srRNAs and tRNA in Leishmania mitochondria.